A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea, Notodontidae) of the Maputo Special Reserve with descriptions of four new species - László, Gyula M.; Schintlmeister, Alexander; Vetina, Alvaro A. (Zootaxa, 2021)
This paper provides the first comprehensive summary of the Notodontidae fauna of the Maputo Special Reserve in southern Mozambique listing 51 species. Four species are described as new to science (Thacona smithi László & Schintlmeister sp. n., Arciera meridiana László & Schintlmeister sp. n., Leptolepida krugeri László & Schintlmeister sp. n., Thaumetopoea latinivea László & Schintlmeister sp. n.) and 23 species are recorded as new country records. Several taxonomic changes are made: the genus Arciera Kiriakoff, 1962 is reinstated and a lectotype is designated for Turnaca grisea Holland, 1893; Thacona pinheyi is transferred to the genus Subscrancia Gaede, 1928 (Subscrancia pinheyi (Kiriakoff, 1965) comb. nov.); and Hoplitis gigas Distant, 1899 is reinstated from synonymy to species rank (Amyops gigas (Distant, 1899) stat. rev.). 106 colour and 40 black and white diagnostic figures are provided including the hitherto unknown females of Archistilbia mlawula Schintlmeister & Witt, 2015 and Eurystauridia iphis Kiriakoff, 1968.